HR Practices Beyond Compliance: Enhancing Organizational Citizenship Behavior in Nepalese Banking - Ghimire, Binod; Magar, Sujan Budathoki (NCC Journal, 2023)
Amidst the ever-changing ICT landscape, shifting employee demographics, and heightened global competition, the efficacy of human resource management (HRM) is an indispensable determinant of organizational success in the current dynamic business environment. In this context, this study investigates the impact of HRM practices on organizational citizenship behavior (OCB) within private commercial banks in Nepal. The study assessed nine HRM aspects, including hiring, compensation, job security, career development, training, performance evaluations, job design, motivation, and work environment, by conducting in-person interviews with 308 banking employees. As a result, job security emerged as the primary determinant of OCB, as evidenced by a 0.298-unit increase in OCB for every one-unit increase in job security, all other variables being held constant. Additionally, the research unveiled the diverse effects of additional HRM elements, including performance appraisal, development and training, compensation and motivation, recruitment and selection, workplace conditions, and job design, all of which contributed to OCB in a decreasing order. With respect to strategic recruitment, meaningful job roles, conducive work environments, effective incentives, career advancement opportunities, fair compensation, comprehensive training, and structured performance evaluations, the research highlights the critical need for Nepalese private commercial banks to implement refined HRM strategies in order to promote OCB and achieve organizational goals.